Value-Sensitive Design Approaches for Emerging Technologies (Journal of Ethics in Emerging Technologies & Society p-ISSN 3117-5996 and e-ISSN 3117-6003, 2024)
Value-sensitive design (VSD) is a theoretically grounded, practically oriented approach to technology design that accounts for human values in a principled and comprehensive manner throughout the design process. Originally developed for information systems and computer-supported cooperative work, VSD has been extended and contested as AI and autonomous systems have emerged as dominant technology design challenges, raising questions about whose values are represented, how value conflicts are resolved, and whether VSD's tripartite methodology -- conceptual, empirical, and technical investigation -- adequately addresses the systemic societal impacts of large-scale intelligent systems. This paper proposes the VSD for Emerging Technologies Framework (VSDETF), a systematic review and critical extension of VSD methodology for five emerging technology domains: conversational AI systems, autonomous decision-making agents, biometric surveillance technologies, personalisation algorithms, and human-robot interaction systems. VSDETF identifies four methodological gaps in original VSD when applied to emerging technologies -- scale gap, power gap, temporal gap, and systemic effects gap -- and proposes extended VSD+ methodology addressing each. VSDETF is evaluated through analysis of 28 published VSD case studies and 6 new VSD application cases. Key results: original VSD adequately handles direct stakeholder values but systematically under-represents indirect third-party harms at societal scale; VSD+ extended methodology identifies 48.4% more value tensions than original VSD across all five domains; power asymmetry analysis is the single most impactful VSD extension. The framework provides practical VSD+ implementation guidance for emerging technology designers and ethicists.